News and Markets in the Time of COVID-19 - Mamaysky, Harry (Journal of Financial and Quantitative Analysis, 2024)
Abstract The onset of COVID-19 was characterized by voluminous, negative news. Higher narrativity news topics (measured by textual proximity to articles describing the 1987 stock market crash and textual distance from Federal Reserve communications) were systematically associated with contemporaneous market responses, which were larger on high volatility days (hypersensitivity), and with markets–news feedback. Hypersensitive news topic-market pairs were associated with next-day reversals. A test using the news–markets relationship identifies a mid-March 2020 structural break, which was knowable by the end of April. Post break, markets and news became considerably less coupled, and hypersensitivity and reversals abated.